Control of blood pressure in the cold: differentiation of skin and skeletal muscle vascular resistance. Issue 1 (25th October 2022) - Mugele, Hendrik; Marume, Kyohei; Amin, Sachin B.; Possnig, Carmen; Kühn, Lucie C.; Riehl, Lydia; Pieper, Robin; Schabbehard, Eva‐Lotte; Oliver, Samuel J.; Gagnon, Daniel; Lawley, Justin S.
Abstract : New Findings: What is the central question of this study? Why does blood pressure increases during cold air exposure? Specifically, what is the contribution of skin and skeletal muscle vascular resistance during whole body versus isolated face cooling? What is the main finding and its importance? Whole‐body cooling caused an increase in blood pressure through an increase in skeletal muscle and cutaneous vascular resistance. However, isolated mild face cooling caused an increase in blood pressure predominately via an increase in cutaneous vasoconstriction. Abstract: The primary aim of this investigation was to determine the individual contribution of the cutaneous and skeletal muscle circulations to the cold‐induced pressor response. To address this, we examined local vascular resistances in the cutaneous and skeletal muscle of the arm and leg. Thirty‐four healthy individuals underwent three different protocols, whereby cold air to clamp skin temperature (27°C) was passed over (1) the whole‐body, (2) the whole‐body, but with the forearm pre‐cooled to clamp cutaneous vascular resistance, and (3) the face. Cold exposure applied to the whole body or isolated to the face increased mean arterial pressure (all, P  < 0.001) and total peripheral resistance (all, P  < 0.047) compared to thermal neutral baseline. Whole‐body cooling increased femoral ( P  < 0.005) and brachial artery resistance ( P  < 0.003) compared to thermoneutral baseline. Moreover, when the forearm was pre‐cooled to remove the contribution of cutaneous resistance ( P  = 0.991), there was a further increase in lower arm vasoconstriction ( P  = 0.036) when whole‐body cooling was superimposed. Face cooling also caused a reflex increase in lower arm cutaneous ( P  = 0.009) and brachial resistance ( P  = 0.050), yet there was no change in femoral resistance ( P  = 0.815) despite a reflex increase in leg cutaneous resistance ( P  = 0.010). Cold stress causes an increase in blood pressure through a change in total peripheral resistance that is largely due to cutaneous vasoconstriction with face cooling, but there is additional vasoconstriction in the skeletal muscle vasculature with whole‐body cooling.